Conventionalised impoliteness strategies used by main characters along with their metapragmatic comments in the Instant Family movie - Binti Qani'ah (Pioneer: Journal of Language and Literature, 2025)
This study investigated the use of conventionalised impoliteness strategies and their metapragmatic comments employed by the main characters in the Instant Family (2018) movie. Using Culpeper’s (2011) framework of impoliteness, the study identified nine types of conventionalised strategies and examined how hearers evaluated them through verbal and nonverbal metapragmatic responses. In addition, a descriptive qualitative method was applied to analyze the interactions among the Wagner family members, uncovering patterns of impolite utterances and their social dynamics. The result showed that the most frequently used conventionalised impoliteness strategies were direct insults, pointed criticisms, and unpalatable questions, which Ellie and Lizzy mainly employed. At the same time, Juan did not display any impoliteness, indicating a gender-based distribution. These strategies were responded to through various metapragmatic responses, including verbal forms such as denials, justifications, and counter-attacks, as well as nonverbal expressions. In conclusion, it highlighted the contextual nature of impoliteness and suggested that family-based narratives offered a rich foundation for examining pragmatic phenomena in everyday interactions.